Child and maternal health predictors of physical, social/emotional and learning outcomes in infants and preschoolers - Smith, K; Sanson, A; Wake, M; Berthelsen, D (My University, 2008)
This study aimed to determine the relative impact of mothers' and children's health exposure on Australian children's physical, social/emotional, and learning outcomes. Cross-sectional analyses of Wave 1 data from the Longitudinal Study of Australian Children (LSAC) involving 5107 infants and 4983 4-5 year olds. In multivariable analyses adjusted for sociodemographic variables, we examined associations between prenatal, postnatal and current child and maternal health on the LSAC Outcome Index (OI). The OI is a composite measure which includes an overall Index as well as three separate domain scores, tapping physical development, social and emotional functioning, and learning and cognitive development. Infants and children experienced substantial physical health problems, e.g. low birth weight (5%), pre-term birth (7%), special health care needs (14%), overweight/obesity (21%), and asthma (15%). Current (eg asthma and healthful nutritional behaviours) and perinatal (pre-term birth) problems predicted lower OI scores, especially for the 4-5 year olds. Serious psychological distress among mothers predicted poorer, and better maternal general health and enjoyment of physical activity predicted better, child Outcome Index scores. Pre-natal health, smoking/alcohol use, and meeting nutritional and physical activity guidelines contributed relatively little. Impacts of child health were often greater in the Social-Emotional and/or Learning Domain than in the Physical Domain, emphasising the importance of children's health to all aspects of their functioning. Weaker influences in the first year of life suggest that intervention in the early years (i.e. between infancy and preschool) may help prevent the impacts of poorer health developing.
Keywords: Child Development -- Social; Health; Child Development -- Emotional; Child Development; Health and wellbeing; Childhood and child development; Child Development; Health; Emotional; Social; Childhood and child development; Health and wellbeing